Detecting Sea Ice Leads and Floes in the Northwest Passage Using CryoSat-2 - Amy E. Swiggs; Isobel R. Lawrence; Andy Ridout; Andrew Shepherd (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
Knowledge of sea ice lead and floe density is important for ship navigation, understanding ice pack dynamics, and mapping primary productivity. Furthermore, reliable lead and floe discrimination is essential for the calculation of sea ice freeboard and thickness from satellite altimetry. Despite its value for shipping, the Northwest Passage is commonly excluded from Arctic-wide satellite altimetry sea ice observations owing to the challenges of obtaining accurate retrievals in the region. Here, we map the distribution of leads and floes in the Northwest Passage using Landsat 8 satellite optical imagery, and we use these to evaluate the efficacy of near-coincident classifications from CryoSat-2 satellite radar altimetry. We test different pulse peakiness and stack standard deviation thresholds for discriminating returns from CryoSat-2 into leads and floes and assess the agreement with near-coincident Landsat 8 estimates. CryoSat-2 lead and floe densities are, on average, 14% higher and 45% lower than Landsat 8, respectively. We attribute the difference to a range of factors including the coarser spatial sampling of CryoSat-2 which results in mixed surface types within the radar footprint, off-nadir ranging of leads, and the misidentification of sea ice floes as ambiguous surface type. In particular, we find the poorest agreement in October, when the ice pack is fragile after the summer melt season. We use our findings to develop a bias adjustment to bring CryoSat-2 lead and floe density estimates in line with Landsat 8, reducing the root mean square difference between them from 20% to 5% and 47% to 6%, respectively.